(3HOd GdUaI aj GdhSGWIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3CSGd GdTjN GdCaVd ehdGi hQFjS hef CfG YHOg CWGd Gddg HbGAg JMQi HOd GdUaI GdhSGWI s
(3BNQgG (B:s
(3cPdc GdLSe ai GdMGd ehUha HCfg HGdbhI cPG hcPG hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOS YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs